A Tool to Map Applications to Information Technology Deployment Models. - Fung, Han Ping (2016)
The moment to adopt cloud computing and IT outsourcing for application management is still prevalent. However, there is still lack of research or tool to map an application to a specific IT deployment model like public cloud, private cloud, IT outsourcing or in-house management. This research problem has encouraged the researcher to review literature, developed a Microsoft Excel mapping tool as well as tested it for 26 applications from two organizations in Singapore. This mapping tool is based on 10 criteria to evaluate each application’s characteristics before mapping them to the appropriate IT deployment model. These 10 criteria include: 1) Regulatory Compliance, 2) Vendor Support, 3) Service Availability, 4) Workload Variability, 5) Security, 6) Infrastructure Compatibility, 7) Internet Suitability, 8) Architectures, 9) Financials, and 10) Affinity & Intranet Integration. This article demonstrates that the mapping tool is a valuable asset to both IT management and IT consultant in assessing applications and map them to the correct IT deployment models. The benefits of using this mapping tool include accuracy, consistency and speed in mapping the applications to the appropriate IT deployment models.